TsOH·H2O-mediated N-amidation of quinoline N-oxides: facile and regioselective synthesis of N-(quinolin-2-yl)amides. Issue 34 (13th August 2018) - Chen, Xinghua; Peng, Mei; Huang, Hao; Zheng, Yangfan; Tao, Xiaojun; He, Chunlian; Xiao, Yi
Abstract : An operationally simple method with 100% atom economy was developed for the synthesis of various N -(quinolin-2-yl)amides via the TsOH·H2 O-mediated N -amidation of quinoline N -oxides using inexpensive and commercially available nitriles as the amidation reagents. Abstract : An operationally simple method with 100% atom economy has been developed for the synthesis of various N -(quinolin-2-yl)amides via the TsOH·H2 O-mediated N -amidation of quinoline N -oxides using inexpensive and commercially available nitriles as the amidation reagents. Mechanistic exploration suggested that the reaction probably proceeds through an acid-assisted 1, 3-dipolar cycloaddition and an N–O bond cleavage followed by a dehydro-aromatization process.